logi Saklar Lampu Penerangan Jalan Otomatis Berbasis Timer dengan RTC (Real Time Clock) - Chusnah, Miftachul; Davaudin Saskara, Nouval; Ismail, Isman; Elang Timur Demokrat, Lang; Iqbal Aldiansyah, Muhamad; Maulana Azizii, Ibrah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
In Sidokaton village, public street lighting still needs attention. The condition of street lighting that is sometimes forgotten to be turned on not only endangers the safety of residents but can also hinder economic and social activities. So, it is necessary to introduce and train the application of automatic tools for street lighting that are equipped with a timer using RTC (Real-Time Clock). This tool can be set to turn street lights on and off automatically according to a predetermined time, saving energy and ensuring optimal lighting every night. In this activity program, the target is the community and village government in Sidokaton Village. The implementation of the activity of implementing automatic street lighting technology with a timer using RTC was held at the Sidokaton Village Hall. This activity was attended by 33 participants, consisting of the community and village government officials on August 23, 2024. The implementation of the activity uses the Participatory Action Research method which aims to attract the enthusiasm of the community and the Sidokaton Village government. Community service activities in Sidokaton Village were carried out through several stages, namely coordination with partners (village officials and village communities), preparation of materials and implementation of community service activities through the application of automatic tools for street lighting equipped with a timer using RTC (Real-Time Clock). This activity succeeded in increasing the insight and creativity of the Sidokaton Village community in utilizing technology to improve their quality of life. The participants actively interacted with the speakers and showed a high interest in implementing this technology in their village. The design of an automatic street lighting tool with a timer using RTC is expected to be implemented independently by the village community in the future.